Model Manajemen Sistem Ruang Kerja Virtual Berbasis Google Sites Untuk Meningkatkan Efisiensi Tugas Administrasi Guru - Wahyudi; Sophia Tri Satyawati; Wahyu Agustina Rimbita (LPPM Universitas Pendidikan Mandalika, 2026)
This study aims to develop a Google Sites–based virtual workspace model to enhance the administrative efficiency of early childhood educators. The study employed a Research and Development (R&D) method using the 4D model (Define, Design, Develop, and Disseminate) and applied a concurrent triangulation mixed-methods design. The research participants consisted of 13 kindergarten teachers at TK Kristen 03 Eben Haezer, Salatiga, Indonesia. Data were collected through semi-structured interviews, non-participant observations, questionnaires, and pretest–posttest performance assessments. Qualitative data were analyzed using the interactive model of Miles, Huberman, and Saldaña, including data reduction, data display, and verification. Quantitative data were analyzed using descriptive statistics and paired-sample t-tests. The findings indicate that, prior to the intervention, teachers faced significant challenges, including limited time, fragmented data storage, and ineffective document archiving, resulting in substantial administrative workload demands. The developed virtual workspace integrates key Google Workspace tools (Google Drive, Docs, and Sheets) into a centralized, dashboard-style interface. Validation results confirmed high feasibility, with IT experts rating the system at 95.55% (“very valid”). Practicality assessments from teachers indicated a “very practical” category, while effectiveness testing showed a statistically significant improvement in administrative efficiency, with mean performance scores increasing from 11.76 to 17.53 (p < 0.05). This study demonstrates that a low-cost, integrated digital workspace can significantly reduce administrative burdens, offering a sustainable and scalable solution for resource-limited educational settings.